Clinical and Immunological Study of 30 Cases With Both IgG and IgA Anti-Keratinocyte Cell Surface Autoantibodies Toward the Definition of Intercellular IgG/IgA Dermatosis - Hashimoto, Takashi; Teye, Kwesi; Hashimoto, Koji; Wozniak, Katarzyna; Ueo, Daisuke; Fujiwara, Sakuhei; Inafuku, Kazuhiro; Kotobuki, Yorihisa; Jukic, Ines Lakos; Marinović, Branka; Bruckner, Anna; Tsuruta, Daisuke; et al. (Frontiers in Immunology, 2018)
ABSTRACT Several sporadic cases, in which direct and indirect immunofluorescence studies simultaneously detected IgG and IgA autoantibodies to keratinocyte cell surfaces, have been reported mainly under the name of IgG/IgA pemphigus. However, there have been no systematic studies for this condition. In this study, we collected 30 cases of this condition from our cohort of more than 5000 autoimmune bullous disease cases, which were consulted for our diagnostic methods from other institutes, and summarized their clinical and immunological findings. Clinically, there was no male-female prevalence, mean age of disease onset was 55.6 years, and mean duration before diagnosis this condition was suspected was 18 months. The patients showed clinically bullous and pustular skin lesions preferentially on the trunk and extremities, and histopathologically intraepidermal pustules and blisters with infiltration of neutrophils and eosinophils. Immunologically, ELISAs frequently detected IgG and IgA autoantibodies to both desmogleins and desmocollins. From the characteristic clinical, histopathological and immunological features, which are considerably different from those in classical IgG types of pemphigus, we propose this disease as a new disease entity with preferential name of intercellular IgG/IgA dermatosis (IGAD). This was the largest study of IGAD to date.